Delna obstrukcija dvanajstnika z Laddovim tračkom pri otroku z nonrotacijo črevesja in drugimi prirojenimi malformacijami trebušnih organov - Kotnik, Primož (Medicinski razgledi, 2002)
In the article, the authors present the case of a girl with multiple congenital malformations of the abdominal organs; one of them being duodenal obstruction and the other non-rotation of the intestine, with typical clinicalsymptoms and signs of duodenal obstruction and non-rotation. The importance of diagnostic imaging and co-operation between the pediatric gastroenterologist, radiologist and abdominal surgeon is emphasized. The authors caution that this condition can be associated with high mortality and morbidity rates when it is not recognized early and treated correctly.
Keywords: Duodenalna obstrukcija; Intestinal atresia; Črevesna atrezija; Duodenal obstruction; Dojenček; baby; Congenital; črevesje; Diagnosis; dvanajstnik; Therapy; Infant; obstrukcija; otroci; diagnostika; child